Joining of aluminum and ceramic substrates by interposing molten aluminum–silicon alloy. Issue 2 (6th September 2022) - Kita, Ken'ichiro; Hotta, Mikinori
Abstract: The effects of interposing a molten aluminum alloy layer between pure aluminum and silicon nitride on the strength of joining and properties of the joined sample were investigated. An aluminum‐based alloy containing 12 wt% silicon with a melting point lower than the 660°C melting point of pure aluminum was joined to pure aluminum and a silicon nitride substrate by using polymethylphenylsiloxane. A specimen with the same joining area (1600 mm 2 ) and no alloy layer was prepared for comparison. In thermal cycling tests of Δ190 K, cooled at –40°C and heated at 150°C, the specimen without the alloy layer failed after 200 cycles, whereas the specimen with the alloy layer failed after 500 cycles. The bending strength of the sample with the alloy was approximately 1.5 times that of the sample without the alloy. These results indicate that the alloy layer facilitated the strong joining of the aluminum and substrate.